Investigations and referral for suspected cancer in primary care in New Zealand—A survey linked to the International Cancer Benchmarking Partnership. (20th January 2017) - Htun, H.W.; Elwood, J.M.; Ioannides, S.J.; Fishman, T.; Lawrenson, R.
Abstract : A national internet‐based survey of New Zealand (NZ) primary care physicians ( n  = 192) used the survey instrument developed by the International Cancer Benchmarking Partnership (ICBP). Practitioners were recruited by a range of methods assisted by NZ general practice networks and contacts. Compared to 11 other ICBP jurisdictions, direct access to diagnostic tests was more limited and took more time than in most other areas; the average wait for a test to be done and reported was 3.0 weeks for X‐rays and 8.0 for ultrasound, compared to ICBP averages of 1.6 and 4.7 weeks respectively. Forty‐five per cent of respondents could get specialist advice within 48 hr. Sixty‐six per cent were aware of NZ guidelines for cancer in primary care, and of those 44% consulted them sometimes or often. Access to tests was greater, and time required much less, in the private than the public care system. NZ respondents each answered two of five clinical vignettes, with results similar to other ICBP areas. The survey also included general practice trainees ( N  = 42); their results were similar to the main group. The results suggest that improvements in prompt access to diagnostic tests and referrals for suspected cancer need to be given priority in NZ.